Invisible labour: the role of institutionalised Xenophobia in shaping the experiences of migrant domestic workers in South Africa - Fuman, Melay Asanda (African Cinema Unit, 2026)
Background: Physiotherapy remains a female dominated profession, yet in certain professional spheres female physiotherapists are underrepresented. This is particularly evident in men's professional sport. Despite efforts to promote inclusivity and diversity in various professional men's sports, females in coaching, leadership and support roles remain underrepresented and continue to face significant challenges. While World Rugby, has put policies and development plans in place to address gender inequality, this does not necessarily extend to support staff, like physiotherapists. Lavoi's (2016) socio-ecological model has previously been used to explore the multidimensional barriers that affect the lived experiences of female coaches working in men's sports. However, the experiences of physiotherapists, faced with similar gender challenges, has not been explored. Purpose: This study aimed to identify the challenges and barriers of female physiotherapists working in professional men's rugby union. Guided by the socio-ecological model, it examined the individual, interpersonal, organisational, and sociocultural barriers, and challenges encountered by these therapists, and the facilitators or supports that have made female physiotherapists stay and develop in professional men's rugby union. Methods: A phenomenological qualitative study was undertaken utilising semi-structured interviews. Purposeful criterion sampling was used to identify potential participants who met the inclusion criteria. Participants were recruited through a professional acquaintance of the researcher who is associated with professional men's rugby union. The professional acquaintance was requested to circulate recruitment information to individuals who they identified as prospective participants, who then contacted the researcher. Semi-structured interviews were conducted via Microsoft Teams and transcribed for analysis. A stepwise inductive-deductive thematic analysis was performed to generate an initial list of codes aligned to the four levels of Lavoi's (2016) socio-ecological model. The codes were organised into subthemes by identifying patterns in the coded data and continuously reviewed to identify emerging deductive themes based on the model. Results: Participants included 12 physiotherapists, working globally in professional men's rugby for an average of 5.3 years. The thematic analysis identified 18 higher order themes, categorising them as either barriers or supports. The greatest barriers emerged in the societal and organisational dimensions, while the individual dimension provided the most supporting factors. As individuals, physiotherapists noted significant personal sacrifices which affected their work-life balance and negatively impacted on personal relationships. However, their job rewarded them and provided satisfaction particularly linked to returning athletes to play. At an interpersonal level, participants had a supportive and respectful relationship with the athletes but identified a lack of female role models in rugby union. Organisationally, participants faced significant challenges describing inadequate policies, particularly around maternity leave and family obligations. They were often overlooked and dismissed for better roles. At the societal level, barriers emerged relating to traditional gender roles, gender power dynamics, and gender stereotypes within their teams. Conclusion: Despite policies promoting gender equity in professional men's rugby structures, female physiotherapists working in these environments continue to face gender-related challenges which hinder their representation and career progression. This often forces them into leaving these roles. The findings underscore the importance of implementing and enforcing policy frameworks aimed at increasing female representation and breaking down gendered structures within rugby organisations. At the club level, offering mentorship programs, career progression pathways, and flexible work-life balance options can support female physiotherapists professional growth and retention. Promoting transparency in recruitment processes and increasing the visibility of females in these roles can not only normalise their presence but also inspire greater female representation in the field. Implications: Sporting codes need to improve their structures and policies to better support and retain female physiotherapists, therefore negating the masculine norm within certain sporting disciplines. Female physiotherapists are as capable as their male counterparts of fulfilling these roles and should be presented with equal opportunities to do so.